“The Slimy Mud of Words” Language and New Concepts in Medicine (Res Medica, 2013)
Based on a Dissertation read before the Royal Medical Society on Friday, 24th February, 1961.The condition of man requires that he communicate with his fellows. Yet language may be a distorting glass and may often accentuate the isolation rather than the communication. For the doctor, the need for personal communication is as great as for other men but there are, in addition, two spheres of his professional work in which it becomes paramount.In the first place, the doctor has to contact his patients. "I am by trade a dealer in words, and words, as you know, are the most potent drugs known to man."  The saying is attributed to Rudyard Kipling and contains a truth familiar to all who come in contact with patients. Words acting as drugs influence the irrational and the emotional, and their power is amply demonstrated by the positive results so often produced by the pharmacologically inert tablets used in double blind clinical trials.